EXPERIENCES OF MOTHERS OF TECHNOLOGY-DEPENDENT CHRONIC CHILDREN IN A PEDIATRIC INTENSIVE CARE UNIT - Sousa, Brendo Vitor Nogueira; Silveira, Aline Oliveira; Oliveira, Elenilda Farias de; Martins, Gisele (Cogitare Enfermagem, 2023)
Objective: to describe mothers' experiences and repercussions of the hospitalization of technology-dependent chronic children in a Pediatric Intensive Care Unit on their personal and family life. Method: qualitative study conducted with 11 mothers of technology-dependent chronic children in a public hospital in the Federal District, Brazil. Data were collected by semi-structured interviews, recorded, later transcribed, coded, and subdivided into categories. Thematic content analysis was used as an analysis strategy. Results: were divided into five categories, which express the experiences of prolonged hospitalization, maternal feelings, difficulties/needs, coping strategies, and context of the pandemic, which highlighted the mostly negative repercussions that bring changes in the family dynamics in general, by needing to reinvent themselves and adapt to the conditions of the child and the hospital. Final considerations: the data show family vulnerability and reinforce the importance of nursing work for the adoption of a family-centered care model.